De‐escalating Hate: Muslim Organizations' Counter‐Speech to Buddhist Islamophobia in Sri Lanka (2012–2014) - Johansson, Andreas (CyberOrient, 2025)
In contemporary Sri Lanka, nationalistic Sinhala organizations like Bodu Bala Sena (BBS) have made a great impact on the debate over what role Buddhism should play in the country. BBS claims that Islam is a non‐Sri Lankan element in the Buddhist majority society, campaigning on such issues on social media between 2012 and 2014. This led Sri Lankan Muslim organizations to use social media to counter BBS campaigns, one of many self‐defense strategies the Muslim community uses, including political forums like the parliament and ecumenical discussions among theologians. The focus of this article is on how Muslim organizations use social media in relation to dual nationalism (Muslim) and nation (Sri Lankans) in their reaction toward organizations like BBS. The data analyzed are pictures posted on the Facebook pages of Muslim political organizations between 2012 and 2014.